Superiority of Stent-Grafts for In-Stent Restenosis in the Superficial Femoral Artery: Twelve-Month Results From a Multicenter Randomized Trial. (February 2015) - Bosiers, Marc; Deloose, Koen; Callaert, Joren; Verbist, Jürgen; Hendriks, Jeroen; Lauwers, Patrick; Schroë, Herman; Lansink, Wouter; Scheinert, Dierk; Schmidt, Andrej; Zeller, Thomas; Beschorner, Ulrich; et al.
Purpose: To evaluate the short- and midterm outcomes of the Viabahn endoprosthesis with Propaten Bioactive Surface vs. standard balloon angioplasty for treatment of in-stent restenosis in the superficial femoral artery.Methods: Between June 2010 and February 2012, 83 patients with superficial femoral artery in-stent and Rutherford category 2 to 5 ischemia were enrolled at 7 sites participating in this prospective randomized controlled study (RELINE; ClinicalTrials.gov ; identifier NCT01108861). The patients were randomized to treatment with either the heparin-bonded Viabahn endoprosthesis (n=39: 29 men; mean age 67.7±9.8 years) or a standard angioplasty balloon (n=44: 32 men; mean age 69.0±9.7 years). The primary effectiveness outcome was primary patency at 12 months, defined as no restenosis/occlusion within the target lesion based on duplex ultrasound and no target lesion revascularization. The primary safety endpoint was the incidence of serious device-related adverse events within 30 days of the procedure.Results: All patients randomized to receive dilation or the Viabahn stent-graft were treated according to their assignment. The technical success was 100% for the Viabahn group and 81.8% for the angioplasty group (p=0.002) owing to 9 patients requiring a bailout procedure after unsuccessful angioplasty. The 12-month primary patency rates were 74.8% for the Viabahn group and 28.0% for the angioplasty group (p<0.001). Excluding the 9 angioplasty patients who received bailout stenting, the primary patency for optimal balloon angioplasty was 37.0% (p<0.001). Three patients experienced device-related adverse events within 30 days: occlusion of the target lesion (Viabahn group), peripheral embolization (angioplasty group), and reocclusion of the target lesion (angioplasty group).Conclusion: In this study, the treatment of femoropopliteal in-stent restenosis with a Viabahn endoprosthesis showed significantly better results than treatment with a standard balloon at 1 year.